Evaluasi Struktur Jembatan Gantung Pejalan Kaki Dumpoh, Magelang Jawa Tengah - Algazt Aryad Masagala (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2023)
The bridge analyzed is a suspension type with a function as a pedestrian bridge. The bridge has a total span of 53.75 m and a width of 1.8 m, steel construction with wooden deck. The service life factor, damage to the bridge frame, and overload are certainly a problem for this bridge structure. Evaluation of the structure using survey data from existing measurements at the bridge location, then analyzed using the SAP2000 program. The result is that all tower frames, girders, main cables, hangers, and bridge decks, the nominal capacity is still able to withstand the ultimate load. However, the deflection in the middle of the bridge span is 0.72 m and has exceeded the allowable deflection (L/200). So based on the results of the evaluation of the Dumpoh suspension bridge structure, the cross-sectional strength of the frame is still safe, but the stiffness of the deflection value does not meet.